ORGANIZATIONAL CULTURE AND MANAGERIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN YENAGOA, BAYELSA STATE - Olunta, Ayebaesin; Nwokocha, Ify Harcourt (Scholars Digest Publishing, 2025)
The study examines the influence of organizational culture on Managerial performance in deposits money banks in Yenagoa monopolies. Descriptive survey design method was adopted for the study. In line with the objectives of the Study, Spearman Rank Order Correlation Co-efficient was used to test the hypothetical relationship on the predictor and criterion variables. On the basis of this finding, it was concluded that, Organizational Culture actually give rise to managerial performances. This study recommends that, bank Managers should recruit employees with clear vision and inspirational leadership qualities attributes, also bank leaders should enhance their motivations strategies. This study reveal that organizational culture describes cultural values system and transformational Leadership has positively correlation with managerial performances in money depots bank is Yenagoa Bayelsa state.